Persistent organic pollutants and gestational diabetes: A multi-center prospective cohort study of healthy US women. (March 2019) - Rahman, Mohammad L.; Zhang, Cuilin; Smarr, Melissa M.; Lee, Sunmi; Honda, Masato; Kannan, Kurunthachalam; Tekola-Ayele, Fasil; Buck Louis, Germaine M.
Abstract: Background: Persistent organic pollutants (POPs) are linked with insulin resistance and type-2 diabetes (T2D) in the general population. However, their associations with gestational diabetes (GDM) are inconsistent. Objective: We prospectively evaluated the associations of POPs measured in early pregnancy with GDM risk. We also assessed whether pre-pregnancy BMI (ppBMI) and family history of T2D modify this risk. Methods: In NICHD Fetal Growth Study, Singletons, we measured plasma concentration of 76 POPs, including 11 organochlorine pesticides (OCPs), 9 polybrominated diphenylethers (PBDEs), 44 polychlorinated biphenyls (PCBs), and 11 per -and polyfluoroalkyl substances (PFAS) among 2334 healthy non-obese women at 8–13 weeks of gestation. GDM was diagnosed by Carpenter and Coustan criteria. We constructed chemical networks using a weighted-correlation algorithm and examined the associations of individual chemical and chemical networks with GDM using multivariate Poisson regression with robust variance. Results: Higher concentrations of PCBs with six or more chlorine atoms were associated with increased risk of GDM in the overall cohort (risk ratios [RRs] range: 1.08–1.13 per 1-standard deviation [SD] increment) and among women with a family history of T2D (RRs range: 1.08–1.48 per 1-SD increment) or normal ppBMI (RRs range: 1.08–1.22 per 1-SD increment). Similar associations were observed for the chemical network comprised of PCBs with ≥6 chlorine atoms and the summary measure of total PCBs and non-dioxin like PCBs (138, 153, 170, 180). Furthermore, four PFAS congeners - perfluorononanoic acid (PFNA), perfluorooctanoic acid (PFOA), perfluoroheptanoic acid (PFHpA), and perfluorododecanoic acid (PFDoDA) - showed significant positive associations with GDM among women with a family history of T2D (RRs range:1.22–3.18 per 1-SD increment), whereas BDE47 and BDE153 showed significant positive associations among women without a family history of T2D. Conclusions: Environmentally relevant levels of heavily chlorinated PCBs and some PFAS and PBDEs were positively associated with GDM with suggestive effect modifications by family history of T2D and body adiposity status. Highlights: Epidemiological evidence for associations between POPs and GDM is inconsistent. We prospectively evaluated the associations of POPs with GDM among 2334 healthy US pregnant women. Heavily chlorinated PCBs and some PFAS and PBDEs were positively associated with GDM. Family history of type 2 diabetes and pre-pregnancy BMI appeared to modify the risk.